Before & after a whole house of faux painting demonstrations! ([Long Beach, Calif.?] Faux Fun, 2004)
Demonstrates a number of textured finishes for interior walls. Techniques covered in program: crosshatching; water stain glazing; antique glazing; abstract brushing; distressed paint finish; fan texture; antique texturing; Picasso sponge; glazing with angel prints.
DVD
Introduction program.
Cross hatching--.
Water stain glazing--.
Antique glazing--.
Rag whipping--.
Keywords: House painting; Texture painting; Interior walls -- Decorations; Finishes and finishing; Furniture painting